Civil-law responsibility in sphere of maintenance of chemical safety (Journal of actual problems of jurisprudence, 2018)
In given article are considered questions of definition civil-law responsibility in sphere of maintenance of chemical safety. Civil responsibility – a system of property-related measures force applied to violators of civil rights and obligations with a view to restore the situation that existed prior to the offense. Key words: chemical safety, chemicals, civil law, legal regulation, legal support